Cell lines of the same anatomic site and histologic type show large variability in intrinsic radiosensitivity and relative biological effectiveness to protons and carbon ions. Issue 6 (9th May 2021) - Flint, David B.; Bright, Scott J.; McFadden, Conor H.; Konishi, Teruaki; Ohsawa, Daisuke; Turner, Broderick; Lin, Steven H.; Grosshans, David R.; Chiu, Hua‐Sheng; Sumazin, Pavel; Shaitelman, Simona F.; Sawakuchi, Gabriel O.
Abstract : Purpose: To show that intrinsic radiosensitivity varies greatly for protons and carbon (C) ions in addition to photons, and that DNA repair capacity remains important in governing this variability. Methods: We measured or obtained from the literature clonogenic survival data for a number of human cancer cell lines exposed to photons, protons (9.9 keV/μm), and C‐ions (13.3–77.1 keV/μm). We characterized their intrinsic radiosensitivity by the dose for 10% or 50% survival (D10% or D50% ), and quantified the variability at each radiation quality by the coefficient of variation (COV) in D10% and D50% . We also treated cells with DNA repair inhibitors prior to irradiation to assess how DNA repair capacity affects their variability. Results: We found no statistically significant differences in the COVs of D10% or D50% between any of the radiation qualities investigated. The same was true regardless of whether the cells were treated with DNA repair inhibitors, or whether they were stratified into histologic subsets. Even within histologic subsets, we found remarkable differences in radiosensitivity for high LET C‐ions that were often greater than the variations in RBE, with brain cancer cells varying in D10% (D50% ) up to 100% (131%) for 77.1 keV/μm C‐ions, and non‐small cell lung cancer and pancreatic cancer cell lines varying up to 55% (76%) and 51% (78%), respectively, for 60.5 keV/μm C‐ions. The cell lines with modulated DNA repair capacity had greater variability in intrinsic radiosensitivity across all radiation qualities. Conclusions: Even for cell lines of the same histologic type, there are remarkable variations in intrinsic radiosensitivity, and these variations do not differ significantly between photon, proton or C‐ion radiation. The importance of DNA repair capacity in governing the variability in intrinsic radiosensitivity is not significantly diminished for higher LET radiation.